Levoglucosan Emission From Different Indigenous and Exotic Plant Species in Bangladesh - Jahan, K; Jeba, F; Islam, MS; Salam, A (Journal of Biodiversity Conservation and Bioresource Management, 2021)
Levoglucosan is a biomarker for biomass burning with high emission efficiency. Both indigenous and exotic plant species (biomass) are common in Bangladesh and used as a fuel source in rural areas for cooking purposes. Three indigenous plants, Mango (Mangifera indica), Jackfruit (Artocarpus heterophyllus), Coconut (Cocos nucifera) and three exotic plants, Mahogany (Swietenia mahagoni), Koroi (Albizia lebbeck), Guava (Psidium guajava), were selected for this experiment. The study was carried out to determine and compare the levoglucosan emission for these selected indigenous and exotic plants upon burning at the typical rural cooking stove in the laboratory scale. PM10 samples were collected on top of the cooking stove using a low volume air sampler (LVAS). The concentration was determined quantitatively by UV-visible spectrophotometer using anthrone-sulfuric acid reagent. The exotic plant samples (7.47 mg/m3) emitted a higher concentration of levoglucosan than the indigenous plant samples (6.49 mg/m3). Among the six different leaf samples, S. mahagoni leaves showed the highest emission of levoglucosan (6.31 mg/m3) and C. nucifera leaves showed the lowest levoglucosan (5.74 mg/m3) due to their individual cellulose content and combustion efficiency. Among the six wood samples, S. mahagoni woods showed the maximum concentration (9.63 mg/m3) and C. nucifera coir showed the minimum concentration (6.631 mg/m3) of levoglucosan emission. The soft leaf samples (6.02 mg/m3) showed lower emission than the hardwood (7.97 mg/m3) samples because of their diverse structural pattern and combustion efficiency. Comparing the emission factors, the exotic wood and leaf samples (EF=2.89*10– 3g/kg) showed higher emission than the indigenous wood and leaf samples (EF=2.55*10–3g/kg) J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(2): 1-10